Correction: Thiamine analogues as inhibitors of pyruvate dehydrogenase and discovery of a thiamine analogue with non-thiamine related antiplasmodial activity. Issue 1 (14th December 2022) - Chan, Alex H. Y.; Fathoni, Imam; Ho, Terence C. S.; Saliba, Kevin J.; Leeper, Finian J.
Abstract : Correction for 'Thiamine analogues as inhibitors of pyruvate dehydrogenase and discovery of a thiamine analogue with non-thiamine related antiplasmodial activity' by Alex H. Y. Chan et al., RSC Med. Chem., 2022, 13, 817–821, ; https://doi.org/10.1039/D2MD00085G .